Development Of Waste Sorting Technology for Pet and HDPE Plastic Bottles For The Production Of Recycled Plastic Seeds - Santosa Budiono, Herru; Purnomo, Sigit Joko; Taufik, Ikhwan (Politeknik Piksi Ganesha Indonesia, 2023)
Plastic bottle waste is a problem that always arises. In Indonesia, the processing of plastic bottle waste still needs to be improved. Plastic bottle waste can be converted into plastic pellets with economic value. The type of plastic and the colour must be sorted to get quality plastic pellets. A machine is designed to sort out the types of plastic bottle waste, polyethene terephthalate (PET) and high-density polyethene (HDPE). The result is a prototype plastic biotol waste sorting machine with a 41 kg/hour capacity. The prototype of this machine can sort out plastic bottle waste and those not included in the plastic bottle waste category. The results show that the colour sensor and object sensor work optimally to sort plastic bottle waste according to the program.